Uporaba rehabilitacijskih nalog v navideznem okolju - Cikajlo, Imre (Informatica Medica Slovenica, 2010)
Application of virtual reality technology in rehabilitation enables development of target-based rehabilitation tasks. Combined with modern telecommunication technology, it is aimed at establishing a novel service called telerehabilitation, which would enable continuation of rehabilitation at subject's home. The paper presents the potential telerehabilitation service using a virtual environment and addresses the issue whether results comparable with clinical rehabilitation can be achieved, such as improvement of balance after stroke. The results of a pilot study on six volunteers indicate that the effects achieved using a dynamic-balance training device in domestic environment can be comparable to those achieved in the clinical setting.
Keywords: balance; možganska kap; navidezno okolje; ravnotežje; rehabilitacija na daljavo; stroke; telerehabilitacija; telerehabilitation; virtual environment